Conserving Bali’s heritage sites: The power of unwritten laws - Chong, Daniel Ka Leong *; Lai, Mun Loon * (Tourism Educatiors Association of Malaysia, 2018)
This study examines the efforts of heritage conservation on Bali Island specifically in heritage sites. The Global Sustainable Guidelines published by UNESCO were used as areas of assessment as well as the benchmarks for results analysis. A total of four areas of conservation components introduced by UNESCO - Hoi An Protocols: 1) Identification and Documentation, 2) Safeguarding Tangible Aspects, 3) Safeguarding Intangible Aspects and 4) Heritage and the Community were examined. This study applied three research techniques: (1) Secondary Data Analysis, 2) In-depth Interviews, and (3) Site observation in collecting data pertaining to laws, policies, strategies, guidelines, perceptions, and tangible evidences of conservation efforts in Bali. A total of twelve reports pertaining to heritage governance in Bali, five local tourism experts, and five heritage sites were sampled for analysis, interview, observation and evaluation. Thematic analysis was conducted to examine the performance of each heritage conservation area followed by benchmarking analysis to conclude on the level of compliance against the standards suggested by UNESCO. Findings suggested that the conservation efforts vary according to areas, with standardisation of laws and enforcement basically non-existent. Hence, the results indicate a concerning gap in law enforcement and execution of heritage conservation on Bali Island. Interestingly, the local community do not show much concern over heritage deterioration. They place great confidence over unwritten laws which are passed down from generation to generation concerning ways of conserving both tangible and intangible heritage. This study has contributed to the understanding of heritage sites conservation on Bali Island. Moreover, this study provides practical and realistic implications that could improve the governance of site heritage conservation on Bali Island